Analysis of The Effectiveness of Integrated Digital Marketing Communication Strategies in Building MSMEs Brand Awareness Through Social Media - Sulistyo Budi Utomo; Jefri Putri Nugraha; Endang Sri wahyuningsih; Rachmadi Indrapraja; Feliks Anggia Binsar Kristian Panjaitan (SEULANGA SYSTEM PUBLISHER, 2023)
This research aims to analyze the stages of implementing an integrated marketing communications strategy for MSMEs to build brand awareness through Instagram social media. The paradigm used is a constructivist paradigm. The research approach used is a qualitative-descriptive approach. The instruments for this research are observation, interviews, and documentation studies. Data processing is carried out by recording the results of observations, interviews and documentation studies, as well as identifying problems and planning. The data analysis technique used by researchers is a qualitative data analysis technique, referring to the technique proposed by Miles and Huberman, namely the interactive model. This technique consists of the following three components: data reduction, data presentation, and drawing and verifying conclusions. It can be concluded that in public relations and publicity activities, MSMEs do not have a public relations division. Therefore, all control is still held by the marketing division. As for publicity, MSMEs use Instagram as their main means of conveying information. Judging from the conclusions that the researchers have presented, there is a match between the concept or theory regarding integrated marketing communication strategy and the marketing communication strategies that SMEs implement in the field. However, there is one element that is not implemented, namely the public relations element, because it is still part of the marketing division, but regarding publicity, SMEs use Instagram as their publicity medium.